2010
DOI: 10.1111/j.1399-5448.2009.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition from pediatric to adult diabetes care: smooth or slippery?

Abstract: de Beaufort C, Jarosz‐Chobot P, Frank M, Frank M, de Bart J, Deja G. Transition from pediatric to adult diabetes care: smooth or slippery? Objectives: The purpose of this study is to evaluate the practices of diabetes health care providers concerning the transition from pediatric to adult diabetes care. The information presented here may help increase awareness of the organization of transitional care for young people with diabetes and prevent the loss of follow‐up during this vulnerable period in their lives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 16 publications
4
50
0
3
Order By: Relevance
“…15 A 2007 survey of pediatric diabetes centers in 36 countries found that most centers did not have a structured transition care program. 16 This suggests important deficiencies in transition care, but inferences are limited by a low 16% response rate. 16 We were able to conduct in-depth interviews with key respondents at 12 of 15 pediatric diabetes centers in Quebec in the present study, permitting us to address important knowledge gaps in pediatric care providers' perspectives on transition care.…”
Section: Transfer Completionmentioning
confidence: 99%
“…15 A 2007 survey of pediatric diabetes centers in 36 countries found that most centers did not have a structured transition care program. 16 This suggests important deficiencies in transition care, but inferences are limited by a low 16% response rate. 16 We were able to conduct in-depth interviews with key respondents at 12 of 15 pediatric diabetes centers in Quebec in the present study, permitting us to address important knowledge gaps in pediatric care providers' perspectives on transition care.…”
Section: Transfer Completionmentioning
confidence: 99%
“…4,5 Transfer to adult-oriented health services occurs in late adolescence (around age 18 years) and may exacerbate these high-risk behaviors. 6 These periods of nonadherence to medications, clinic appointments, and routine blood work may lead to detrimental and sometimes irreversible outcomes. [7][8][9] Therefore, adolescence and emerging adulthood in general, as well as the time after transfer of care in particular, are critical periods.…”
mentioning
confidence: 99%
“…Transition from pediatric to adult health care for adolescents with type 1 diabetes is suggested to occur between the ages of 14 to 25 (de Beaufort, Jarosz-Chobot, Frank, de Bart, & Deja, 2010). Median age of transition is 20.1 years (Lotstein et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Median age of transition is 20.1 years (Lotstein et al, 2013). The majority of providers (90%) are in agreement that transition planning should begin at least one year prior to transition (de Beaufort, et al, 2010). Reasons for transition to adult care are topped by the patient's wish to transition followed by suggestion to transition given by the treating pediatric provider (Neu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%